Formation of an Integrated Task Force on Gang Activity and Mass Organizations in Response to Escalating Domestic Threats in Jakarta - Marta, Dwi Jati (Ministry of Home Affairs, 2026)
This study examines the transformation of mass organizations into actors of collective violence and evaluates the effectiveness of the Integrated Task Force on Gang Activity and Mass Organizations as a policy response to emerging non-traditional security threats in Jakarta. This study employed a descriptive qualitative case study. Data were collected through interviews, observation, and document analysis, then analyzed using NVivo 12 Plus to examine stakeholder perceptions. The findings indicate that this transformation is driven by symbolic conflict, competition over informal economic resources, and weak state oversight. In response, some mass organizations adopt quasi-militaristic characteristics and use violence to assert control over public spaces. The task force serves as a strategic intervention to address regulatory gaps and restore public order. However, its implementation faces challenges related to legitimacy, transparency, and the risk of political misuse. Divergent perceptions persist: government and business actors support stricter enforcement, while civil society groups express concern about potential abuse of authority. This study recommends strengthening the legal framework, increasing public participation, and applying evidence-based policy evaluation to improve accountability and support sustainable social integration.